THE ROLE OF IRONY IN EXPRESSING IMPOLITENESS - Aytemiz Abbas Abbasova (International Journal of Innovative Technologies in Social Science, 2024)
This paper studies the ways in which verbal irony can be used as an impoliteness tool. From this aspect verbal irony is investigated as a politeness means or an impoliteness tool depending on the strength of criticism, in this case the main matter is equality and inequality in interlocutors’ status. In this case face-saving, face-aggravating strategies happen. The other feature related to verbal irony, its intentionality is studied for intended and unintended irony. Intended and unintended irony is classified as planned and unplanned irony. Irony is analyzed as a linguistics means of impoliteness in the case of over-politeness, for the feature of self-image save and the character of its cancellability. There is little research about irony as an impoliteness tool, or the impolite function of irony, its intentionality, examining the strength of irony depending on the interlocutor’s power differences. In this paper, verbal irony will not be discussed with other types of irony, i.e., situational, dramatic.